Blockchain-Based Agribusiness Digitalization Strategy for Transparency and Traceability of Organic Products - Harsela, Chiska Nova (Politeknik Siber Cerdika Internasional, 2026)
Background: The organic agriculture sector faces critical challenges in ensuring product authenticity, supply chain transparency, and consumer trust. Objective: This study proposes an innovative blockchain-based digitalization strategy integrating smart contracts, IoT sensors, and decentralized consensus mechanisms to enhance traceability and transparency in organic product supply chains. Methods: Employing a mixed-method approach combining design science research with quantitative analysis across 45 organic farming enterprises and 12 distribution networks in Indonesia, this research develops a novel Hybrid Blockchain Architecture (HBA) that synergizes permissioned and public blockchain layers. Results: The HBA framework demonstrates 94.7% improvement in traceability accuracy, 87.3% reduction in verification time, and 23.4% increase in consumer willingness-to-pay for certified organic products. The novelty lies in the integration of multi-stakeholder consensus algorithms adapted for smallholder farming contexts, real-time IoT-enabled quality monitoring, and tokenized incentive mechanisms for supply chain participants. Results indicate that blockchain implementation enhances not only technical transparency but also social capital among supply chain actors through distributed trust mechanisms. Conclusion: This study contributes to digital transformation theory in agriculture by demonstrating how blockchain technology can address information asymmetries while empowering smallholder farmers through inclusive governance structures. Practical implications include scalable implementation frameworks for developing countries and policy recommendations for blockchain-enabled agricultural certification systems.